PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) DI SD/MI - Hidayati, Kurnia (STAIN Ponorogo, 2013)
Abstract: PMRIÂ is a realistic mathematics education which employs real life problems that are considered appropriate to the studentsâ minds. PMRI is developed with reference to constructivist philosophy. PMRI is in line with the new paradigm of education in Indonesia, which is to improve the quality of mathematics education that is solely dominated by the issue on how to improve studentsâ understanding of mathematicsand develop reasoning skill. In this regard, the real world is mainly used as a starting point for the development of ideas and concepts of Mathematics. The role of teacher is only as a guide and facilitator for students in the process of reconstructing their ideas and concepts of Mathematics. Additionally, through the learning activities assisted by the teacher, it is expected that students can find the characteristics, definitions, theorems, or rules themselves. Students are encouraged to understand mathematics through real-world contexts frequently faced or the things that can be possibly imagined by them. Mathematics learning cannot be separated from its nature when someoneattempts to search a problem, solve the problem and organize the subject matter. Hence, Mathematics learning should be directed to the use of situations and opportunities thatallow students to reinvent mathematics by their own efforts.